Regenerated flame-retardant polyphenyl plastic material and method

By adding specific organic compounds and inorganic fillers to the recycled polystyrene plastic material and combining fine process processing, the mechanical properties, flame retardant properties and sound insulation effects of the material are improved, and the problem of insufficient performance in the existing technology is solved, and environmental protection is achieved. Efficient building materials solutions.

CN119119646APending Publication Date: 2024-12-13HUNAN ZHONGKE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593121.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing recycled polyphenylene plastic materials have shortcomings in terms of mechanical properties, durability, flame retardant properties and sound insulation properties, which are difficult to meet the high standard needs of the construction industry. The problem of waste polyphenylene plastic treatment is prominent, affecting the environment and resource utilization.

Method used

Use regenerated flame retardant polyphenylene plastic materials containing specific organic compounds, glass fibers, inorganic fillers, flame retardant and sound insulation compounds. Through fine process processing and the synergistic effect of components, the mechanical properties, flame retardant and sound insulation effect of the material is improved. And reduce resource waste through environmentally friendly recycling.

Benefits of technology

It achieves high mechanical properties, good flame retardant properties, excellent sound insulation and good durability of the materials, meets the construction industry's demand for multifunctional materials, reduces resource waste and environmental pollution, and provides a safer and more comfortable living environment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of materials, in particular to a regenerated flame-retardant polyphenyl plastic material and a method thereof.The regenerated flame-retardant polyphenyl plastic material is prepared from waste polyphenyl plastic particles, an organic compound C, an organic compound D, a sound insulation compound Z, glass fibers, inorganic filler, a flame retardant, a coupling agent and a stabilizer. The multifunctional integration successfully integrates multiple functions of regeneration, flame retardance, sound insulation and the like into one material, the complex process that multiple single-function materials are used for combination in building construction is avoided, the construction cost and difficulty are reduced, the quality and efficiency of building engineering are improved, the requirement of modern buildings for material multifunctionality is met, and the material has a wide application prospect. Compared with a traditional regenerated polyphenyl plastic material, the regenerated polyphenyl plastic material has obvious advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building wall materials, and in particular to a recycled flame-retardant polystyrene plastic material and a method. Background Art

[0002] With the acceleration of global urbanization and the rapid development of the construction industry, the demand for building materials has shown a trend of sustained growth. Polystyrene plastic is a material widely used in the construction field. It has good insulation, light weight, and easy processing. It plays an important role in building walls, insulation materials, decorative materials, etc. However, the problem of handling waste polystyrene plastics is particularly prominent.

[0003] On the one hand, polystyrene plastics have high chemical stability and are difficult to degrade in the natural environment. The long-term accumulation of a large number of discarded polystyrene plastic products not only occupies precious land resources, but these discarded plastics may enter the soil, water and other environments, affecting the fertility and air permeability of the soil, hindering the penetration of water, and having a negative impact on plant growth and the balance of the ecosystem. At the same time, discarded polystyrene plastics that enter the water body will also cause harm to aquatic life.

[0004] On the other hand, existing recycled polystyrene plastic materials have many deficiencies in performance and are difficult to meet the increasingly stringent standards of the construction industry and people's requirements for the quality of living and working environments. In terms of mechanical properties, the strength of traditional recycled polystyrene plastic materials needs to be improved. Their tensile strength, bending strength and impact strength often cannot meet the needs of some building parts with high structural strength requirements. They are prone to deformation and cracking during use, affecting the overall stability and safety of the building.

[0005] Durability is also a key issue. In the long-term use process, the existing recycled polystyrene plastic materials are easily affected by natural factors such as ultraviolet radiation, temperature changes, humidity changes, etc., which will cause aging and degradation, resulting in a gradual decline in the performance of the material and a shortened service life.

[0006] Flame retardant properties are crucial for building materials. However, the flame retardant properties of many recycled polystyrene plastic materials are not ideal. They are easy to burn and burn quickly when a fire occurs, releasing a lot of heat and toxic gases. Traditional flame retardant methods often add some flame retardants, but these flame retardants may have problems such as large addition amounts, unsatisfactory effects, and certain pollution to the environment, and may also affect other properties of the material.

[0007] In addition, with the improvement of people's living standards and the increasing requirements for the quality of living environment, the sound insulation effect of building wall materials has also received more and more attention. Existing recycled polystyrene plastic materials generally perform poorly in terms of sound insulation performance and cannot effectively block the introduction of external noise, which is very important for some places that have high requirements for a quiet environment.

[0008] In summary, in order to solve the problem of waste polystyrene plastic treatment and meet the demand for high performance of materials in the construction industry, it is of great practical significance to develop a new type of recycled flame-retardant polystyrene plastic material that is both recyclable, flame-retardant, has excellent mechanical properties, good durability and excellent sound insulation. This not only helps to reduce resource waste and environmental pollution, but also provides people with a safer and more comfortable living and working environment. Therefore, the present invention is committed to innovating in material composition and preparation method to overcome the shortcomings of the prior art. Summary of the invention

[0009] The invention provides a recycled flame-retardant polystyrene plastic material and a method. The material comprises the following components in mass ratio: 30-50 parts of waste polystyrene plastic particles, 2-8 parts of an organic compound C, whose chemical name is 3-(2-methoxyphenyl)-5-(4-fluorophenyl)-2-oxo-1,3-oxazolidine-4-carboxylic acid ethyl ester, 1-6 parts of an organic compound D, whose chemical name is 4-(3-aminopropyl)-6-(2-bromophenyl)-2-thio-1,3-pyrazol-5-one, 1-10 parts of a sound-proofing compound Z, whose chemical name is 2-(3-isopropyl-4-hydroxyphenyl)-4-(2-ethoxyethyl)-6-methyl-1,3,5-triazine-1-oxide, 5-15 parts of glass fiber, 15-30 parts of an inorganic filler, 3-10 parts of a flame retardant, 0.5-2 parts of a coupling agent, and 0.3-1.5 parts of a stabilizer.

[0010] On the other hand, the present invention also provides a method for preparing the recycled flame-retardant polystyrene plastic material, comprising the following steps: Step 1: Raw material pretreatment: sort and clean the recycled polystyrene plastics, remove impurities and surface dirt, and then crush them for later use; surface treatment of glass fiber; Step 2: In a reaction kettle, raw material monomer C1 and raw material monomer C2 are added at a molar ratio of 1:1.4, wherein the raw material monomer C1 is 3-carboxy-5-(4-fluorophenyl)-2-oxo-1,3-oxazolidine-4-carboxylic acid ethyl ester, and the raw material monomer C2 is 2-methoxyaniline, and react with concentrated hydrochloric acid as a catalyst. After the reaction is completed, the product is purified and dried to obtain an organic compound C; In another reaction device, a raw material monomer D1 of 4-aminopropyl, a raw material monomer D2 of 6-(2-bromophenyl)-2-thio-1,3-pyrazol-5-one and a solvent D of dimethyl sulfoxide are mixed, and an initiator azobisisobutyronitrile is added to carry out a polymerization reaction. After the reaction is completed, a pure organic compound D is obtained by precipitation, filtration and drying; The synthesized organic compounds C and D are mixed in a mass ratio of 4:3, and an appropriate amount of dispersant sodium polyacrylate is added, and the mixture is stirred evenly in a high-speed stirrer to form an organic compound mixed solution for later use; Step 3: Material mixing and molding, add the pretreated recycled polystyrene plastic particles, glass fiber, inorganic filler, flame retardant, coupling agent, stabilizer and sound insulation compound Z into a high-speed mixer and mix them evenly, then slowly add the organic compound mixed solution prepared in step 2 into the high-speed mixer to fully mix the ingredients, and transport the mixed materials to the extruder for extrusion molding.

[0011] Furthermore, during the synthesis of the organic compound C, the molar ratio of the raw monomers C1 and C2 can be adjusted within the range of 1:1.3-1.5 to adapt to different reaction conditions and product performance requirements.

[0012] Furthermore, during the synthesis of the organic compound D, the amount of the initiator used can vary between 1% and 2% of the total mass of the raw monomers to control the polymerization reaction rate and the quality of the product.

[0013] Furthermore, the mass ratio of calcium carbonate to talc in the inorganic filler can be varied between 1:1 and 3:1 to meet different processing performance and cost requirements.

[0014] Furthermore, the content of magnesium hydroxide in the flame retardant can be adjusted between 50% and 80% of the total mass of the flame retardant to balance the flame retardant properties and other properties of the material.

[0015] Furthermore, the added amount of the sound insulation compound Z can be adjusted between 2% and 8% of the total mass of the material to meet different sound insulation performance requirements.

[0016] Furthermore, when the glass fiber is surface treated in step 1, the mass fraction of the titanate coupling agent solution can be selected between 2% and 3%, the soaking time is 1 to 2 hours, and the drying temperature can be adjusted between 70 and 80°C.

[0017] Furthermore, the synthesis temperature of the organic compound C in step 2 can vary between 50-60° C., the stirring speed can be adjusted between 200-300 rpm, and the reaction time can vary between 6-10 hours.

[0018] Furthermore, in the synthesis process of the organic compound D in step 2, the amount of the solvent can be adjusted between 40%-50% of the total mass of the raw monomer, the polymerization reaction temperature can be varied between 60-70° C., and the reaction time can be varied between 8-12 hours.

[0019] Beneficial technical effects of the invention: The sound insulation compound Z was used for the first time. Its unique chemical structure and acoustic properties give the material an excellent sound insulation effect. It fills the gap in related technologies and provides a new solution for improving the sound insulation performance of building materials. The synergistic effect of organic compounds C and D with other components is integrated. On the basis of maintaining the regeneration and flame retardant properties of the material, the mechanical properties such as strength, stiffness and stability are further improved. The addition of sound insulation compound Z not only enhances the sound insulation performance, but also cooperates with other components to optimize the overall performance, so that the material achieves a good balance and improvement in multiple performance aspects. The process parameters of each link such as organic compound synthesis, raw material pretreatment, and material mixing and molding are precisely set and strictly controlled to ensure the uniform mixing of each component and the full progress of chemical reaction, ensure the stability and consistency of material performance, and improve product quality and production efficiency. Recycling of waste polystyrene plastics as raw materials reduces resource waste and environmental pollution. The entire preparation process focuses on environmental protection, and the product also has good environmental performance during use, making a positive contribution to the green development of the construction industry. The successful integration of multiple functions such as recycling, flame retardancy, and sound insulation into one material avoids the complex process of combining multiple single-function materials in construction, reduces construction costs and difficulty, improves the quality and efficiency of construction projects, and meets the needs of modern construction for the versatility of materials. DETAILED DESCRIPTION

[0020] Example 1 Composition of recycled flame-retardant polystyrene plastic materials Source of recycled polystyrene plastic particles: obtained by collecting discarded polystyrene plastic products and undergoing pre-treatment processes such as screening, cleaning, and crushing. Particle size: controlled within the range of 2-4mm to ensure that it can be evenly mixed with other components in subsequent processing and play a good matrix role.

[0021] Chemical name of organic compound C: 3-(2-methoxyphenyl)-5-(4-fluorophenyl)-2-oxo-1,3-oxazolidine-4-carboxylic acid ethyl ester Structural formula: A carbonyl group is connected to the 2nd position of the oxazolidine ring, a phenyl group is connected to the 3rd position, a methoxy group is connected to the 2nd position of the phenyl group, a carboxylic acid ethyl ester group is connected to the 4th position of the oxazolidine ring, a phenyl group is connected to the 5th position, and a fluorine atom is connected to the 4th position of the phenyl group. Design principle: The carbonyl group and the carboxylic acid ethyl ester group in the molecule can chemically react with the active sites on the surface of the recycled polystyrene plastic particles to form chemical bonds and enhance the interfacial bonding force. The methoxyphenyl and fluorophenyl parts can improve the compatibility and dispersibility of organic compounds in the polystyrene plastic matrix. At the same time, their special structure can also improve the processing performance of the material, reduce the melt viscosity, and facilitate the molding and processing of organic compound D. Chemical name: 4-(3-aminopropyl)-6-(2-bromophenyl)-2-thio-1,3-pyrazol-5-one. Structural formula: A thio group is connected to the 2nd position of the pyrazoline ring, an aminopropyl group is connected to the 4th position, a carbonyl group is connected to the 5th position, and a phenyl group is connected to the 6th position. The phenyl group is connected to a bromine atom at the 2nd position. Design principle: The aminopropyl group can interact with the recycled polystyrene plastic particles to enhance the interface bonding. The thio and pyrazoline structures give the material flame retardant properties, and can form a barrier layer during the combustion process to prevent the spread of flames. The bromophenyl part can increase the rigidity and heat resistance of the material, and comprehensively improve the material performance. The reinforcing fiber is glass fiber (length 4-8mm, diameter 8μm), which has high strength and modulus, can be evenly dispersed in the material system, bear the load, prevent crack expansion, and improve the strength and stiffness of the material. Inorganic fillers include calcium carbonate (particle size 0.2-0.4μm) and talcum powder (particle size 0.1-0.3μm). Inorganic fillers can fill the internal voids of the material, reduce costs, and improve processing performance and dimensional stability.

[0022] In addition to the flame retardant effect of organic compound D, the flame retardant also adds an appropriate amount of traditional flame retardants such as magnesium hydroxide. Magnesium hydroxide decomposes under heat to absorb heat, release water vapor, dilute the concentration of combustible gas and oxygen, and further improve the flame retardant performance. Coupling agents such as titanate coupling agents are used to improve the interface compatibility between inorganic fillers and organic matrices, enhance the bonding force between the two, and improve the comprehensive performance of the material. Stabilizers add an appropriate amount of antioxidants as stabilizers, such as hindered phenol antioxidants, which can absorb free radicals, prevent the material from aging and degradation during long-term use, and improve the stability of the material.

[0023] The chemical name of the sound insulation compound is 2-(3-isopropyl-4-hydroxyphenyl)-4-(2-ethoxyethyl)-6-methyl-1,3,5-triazine-1-oxide. Structural formula: A hydroxyphenyl group is connected to the 2nd position of the triazine ring (an isopropyl group is connected to the 3rd position of the phenyl group, and a hydroxyl group is connected to the 4th position), an ethoxyethyl group is connected to the 4th position, a methyl group is connected to the 6th position, and an oxygen atom is connected to the 1st position of the triazine ring. Design principle: The compound has a unique molecular structure and acoustic properties. The hydroxyl, isopropyl and other groups in its molecules can form hydrogen bonds or other interactions with other components in the material, making it evenly dispersed in the material. At the same time, the presence of the triazine ring structure and oxygen atoms gives the compound special acoustic properties, which can effectively absorb and scatter sound waves, thereby significantly improving the sound insulation effect of the material. Its addition amount accounts for 3%-8% of the total mass of the material.

[0024] Preparation method: Step 1: Raw material pretreatment The recycled polystyrene plastic is classified and cleaned to remove impurities and surface dirt, and then crushed into particles with a particle size of 2-4 mm for standby use. The glass fiber is surface treated, and the fiber surface is etched and activated with appropriate chemical reagents (such as titanate coupling agent solution) to improve its bonding with the matrix. The treated glass fiber is stored in a dry environment to prevent moisture from affecting its performance. Step 2: Synthesis and treatment of organic compounds Synthesis of organic compound C: In a reactor, a specific raw material monomer (raw material monomer C1 is 3-carboxy-5-(4-fluorophenyl)-2-oxo-1,3-oxazolidine-4-carboxylic acid ethyl ester, and raw material monomer C2 is 2-methoxyaniline) and a catalyst (catalyst C is concentrated hydrochloric acid, and the amount used is 2.5% of the total mass of the raw material monomer) are added according to a molar ratio of 1:1.4 (raw material monomer C1: raw material monomer C2). The reaction was carried out at a temperature of 55°C and a stirring speed of 250 rpm for 8 hours. During the reaction, the reaction progress was controlled by monitoring the viscosity of the reaction system (using a rotational viscometer to control the viscosity at 40-70 Pa・s), pH (pH value controlled at 2-3) and other parameters. After the reaction, the product was purified (using a vacuum distillation method to distill and remove unreacted raw materials and by-products at a vacuum degree of 0.07-0.09MPa and a temperature of 70-80°C) and dried (dried in a vacuum drying oven at 55°C for 10 hours) to obtain organic compound C. Synthesis of organic compound D: In another reaction device, raw material monomer D1 (4-aminopropyl), raw material monomer D2 (6-(2-bromophenyl)-2-thio-1,3-pyrazol-5-one) and solvent (solvent D is dimethyl sulfoxide, the amount of which is 45% of the total mass of the raw material monomers) are mixed, and initiator (initiator D is azobisisobutyronitrile, the amount of which is 1.5% of the total mass of the raw material monomers) is added. The polymerization reaction is carried out at a temperature of 65°C for 10 hours. After the reaction is completed, pure organic compound D is obtained by precipitation (the reaction product is poured into excess deionized water for precipitation), filtration, drying (dried in a vacuum drying oven at 75°C for 9 hours) and other processes. The synthesized organic compounds C and D were mixed in a mass ratio of 4:3, and a proper amount of dispersant (the dispersant was sodium polyacrylate, and the amount was 4% of the total mass of the organic compounds) was added, and stirred evenly in a high-speed stirrer at a speed of 900 rpm to form an organic compound mixed solution for use.Step 3: Material mixing and molding. Add the pretreated recycled polystyrene plastic particles, glass fiber, inorganic filler, flame retardant, coupling agent, stabilizer and sound insulation compound Z to a high-speed mixer and mix them evenly at 80°C and 350 rpm for 30 minutes. Then slowly add the organic compound mixed solution prepared in step 2 to the high-speed mixer and continue stirring for 20 minutes to fully mix the ingredients. The mixed materials are conveyed to the extruder and extruded at a screw speed of 105 rpm, an extrusion temperature of 190-210°C and a pressure of 10.5MPa. The extruded sheets or profiles are cut and packaged as needed to obtain the final recycled flame-retardant polystyrene plastic material products.

[0025] Performance test: The mechanical performance test uses a universal material testing machine to conduct tensile, bending and impact tests on the prepared products. The results show that the tensile strength reaches 3.3MPa, the bending strength is 2.7MPa, and the impact strength is 10.5kJ / m², which is significantly improved compared with traditional recycled polystyrene plastic materials and can meet the requirements of building wall materials for mechanical properties. Flame retardant performance test The flame retardant performance test is carried out in accordance with the national standard GB8624-2012 "Classification of Combustion Performance of Building Materials and Products". The test results show that the burning time of the material of the present invention is 36 seconds, the flame spread speed is 0.24m / s, there is no obvious dripping phenomenon, it can meet the B1 flame retardant standard, has good flame retardant performance, and can effectively improve the safety of buildings in the event of fire. Sound insulation performance test uses professional acoustic testing equipment to test the sound insulation performance of the material. In the actual application scenario of simulating building walls, the material of the present invention has a significant improvement in sound insulation effect on sound waves of different frequencies compared with traditional recycled polystyrene plastic materials. For example, for common traffic noise (frequency range of 500-2000Hz), the sound insulation of the material of the present invention can reach 28-33dB, which is 12-17dB higher than that of traditional materials, providing a quieter environment indoors. Durability test The product was placed in an aging test chamber simulating the natural environment for a 60-day durability test, including ultraviolet irradiation (intensity of 50W / m², 8 hours of irradiation per day), humidity changes (humidity cycles between 40%-80%, 4 cycles per day) and temperature cycles (temperature cycles between -10°C and 40°C). After the test, the performance retention rate of the material was above 82% (tensile strength retention rate was 83%, bending strength retention rate was 82%, and impact strength retention rate was 84%), showing good durability and ensuring the stability of the performance of the material during long-term use.

[0026] Example 2

[0027] Raw material preparation Recycled polystyrene plastic particles: Collect waste polystyrene plastic products, wash and crush to obtain particles with a particle size of 2-3mm, prepare 90kg. Organic compound C: Prepare according to the above synthesis method to obtain 6kg. Organic compound D: After synthesis, obtain 4.5kg. Glass fiber: Length 4-8mm, diameter 8μm, prepare 8kg. Calcium carbonate filler: Particle size 0.2-0.4μm, prepare 18kg. Magnesium hydroxide flame retardant: 8kg. Titanate coupling agent: 1.5kg. Hindered phenol antioxidant: 1kg. Sound insulation compound Z: The chemical name is 2-(3-isopropyl-4-hydroxyphenyl)-4-(2-ethoxyethyl)-6-methyl-1,3,5-triazine-1-oxide, prepare 5kg (accounting for 5% of the total mass of the material). Preparation process: Raw material pretreatment: Wash and crush the polystyrene plastic particles to the required particle size, and perform surface treatment on the glass fiber (immerse the glass fiber in a 2.5% mass fraction of titanate coupling agent ethanol solution for 1.5 hours, then take it out and dry it in an oven at 75°C for 3 hours) and then dry it for use. Synthesis and treatment of organic compounds: Prepare organic compounds C and D respectively according to the synthesis process, and mix them evenly to form a solution. Material mixing and molding: Add recycled polystyrene plastic particles, glass fiber, calcium carbonate filler, magnesium hydroxide flame retardant, titanate coupling agent, hindered phenol antioxidant and sound insulation compound Z into a high-speed mixer and mix at 75°C at 400 rpm for 30 minutes. Then slowly add the organic compound mixed solution and continue stirring for 20 minutes. The mixed material is conveyed to the extruder, extruded at a screw speed of 105 rpm, an extrusion temperature of 190-210°C and a pressure of 10.5MPa to obtain a recycled flame-retardant polystyrene plastic material product. Performance test and result analysis The results of the mechanical performance test show that the tensile strength is 3.2MPa, the bending strength is 2.6MPa, and the impact strength is 10.2kJ / m², which meets the expected mechanical performance improvement requirements. The flame retardant performance test meets the B1 flame retardant standard, the burning time is 37 seconds, the flame spread speed is 0.25m / s, and there is no dripping phenomenon, which ensures the flame retardant safety of the material. The sound insulation performance test shows that the sound insulation of common traffic noise reaches 29dB, which is significantly improved compared with traditional materials and meets the sound insulation requirements of buildings. After the durability test, the performance retention rate is above 81% (tensile strength retention rate is 82%, bending strength retention rate is 81%, and impact strength retention rate is 83%), showing good durability.

[0028] The novel sound-insulating building material and the preparation method thereof of the present invention have significant innovation and practicality, can effectively solve the problems existing in the existing sound-insulating materials, and provide a high-performance, multifunctional, environmentally friendly and economical new building material solution for the construction industry. In practical applications, the material formula and preparation process can be appropriately adjusted according to specific engineering requirements to meet the use requirements in different scenarios. At the same time, with the continuous development of materials science, the material of the present invention has the potential to further optimize and expand the application field, such as combining intelligent material technology to achieve adaptive adjustment of sound insulation performance, etc., which provides broad prospects for the development of the field of architectural acoustics.

Claims

1. A recycled flame retardant polystyrene plastic material, It is characterized in that It contains the following components in mass ratio: waste polystyrene plastic particles: 30-50 parts, organic compound C: 2-8 parts, chemical name 3-(2-methoxyphenyl)-5-(4-fluorophenyl)-2-oxo-1,3-oxazolidine-4-carboxylic acid ethyl ester, organic compound D: 1-6 parts, chemical name 4-(3-aminopropyl)-6-(2-bromophenyl)-2-thio-1,3-pyrazol-5-one, sound insulation compound Z: 1-10 parts, chemical name 2-(3-isopropyl-4-hydroxyphenyl)-4-(2-ethoxyethyl)-6-methyl-1,3,5-triazine-1-oxide, glass fiber: 5-15 parts, inorganic filler: 15-30 parts, flame retardant: 3-10 parts, coupling agent: 0.5-2 parts, stabilizer: 0.3-1.5 parts.

2. The method for preparing the recycled flame-retardant polystyrene plastic material according to claim 1, It is characterized in that The following steps are involved: Step 1: Raw material pretreatment, sorting and cleaning the recycled waste polystyrene plastics, removing impurities and surface dirt, and then crushing them for later use; surface treatment of glass fiber; Step 2: In a reaction kettle, raw material monomer C1 and raw material monomer C2 are added at a molar ratio of 1:1.4, wherein the raw material monomer C1 is 3-carboxy-5-(4-fluorophenyl)-2-oxo-1,3-oxazolidine-4-carboxylic acid ethyl ester, and the raw material monomer C2 is 2-methoxyaniline, and react with concentrated hydrochloric acid as a catalyst. After the reaction is completed, the product is purified and dried to obtain an organic compound C; In another reaction device, a raw material monomer D1 of 4-aminopropyl, a raw material monomer D2 of 6-(2-bromophenyl)-2-thio-1,3-pyrazol-5-one and a solvent D of dimethyl sulfoxide are mixed, and an initiator azobisisobutyronitrile is added to carry out a polymerization reaction. After the reaction is completed, a pure organic compound D is obtained by precipitation, filtration and drying; The synthesized organic compounds C and D are mixed in a mass ratio of 4:3, and an appropriate amount of dispersant sodium polyacrylate is added, and the mixture is stirred evenly in a high-speed stirrer to form an organic compound mixed solution for later use; Step 3: Material mixing and molding, add the pretreated recycled polystyrene plastic particles, glass fiber, inorganic filler, flame retardant, coupling agent, stabilizer and sound insulation compound Z into a high-speed mixer and mix them evenly, then slowly add the organic compound mixed solution prepared in step 2 into the high-speed mixer to fully mix the ingredients, and transport the mixed materials to the extruder for extrusion molding.

3. The recycled flame retardant polystyrene plastic material according to claim 1, It is characterized in that During the synthesis of the organic compound C, the molar ratio of the raw monomers C1 and C2 is adjusted within the range of 1:1.3-1.

5.

4. The recycled flame retardant polystyrene plastic material according to claim 1, It is characterized in that During the synthesis of the organic compound D, the amount of the initiator varies between 1% and 2% of the total mass of the raw monomers to control the polymerization reaction rate and the quality of the product.

5. The recycled flame retardant polystyrene plastic material according to claim 1, It is characterized in that The mass ratio of calcium carbonate to talc in the inorganic filler varies between 1:1 and 3:

1.

6. The recycled flame retardant polystyrene plastic material according to claim 1, It is characterized in that The content of magnesium hydroxide in the flame retardant is adjusted between 50% and 80% of the total mass of the flame retardant to balance the flame retardant properties of the material.

7. The recycled flame retardant polystyrene plastic material according to claim 1, It is characterized in that The added amount of the sound insulation compound Z is adjusted between 2% and 8% of the total mass of the material.

8. The preparation method according to claim 2, It is characterized in that When the glass fiber is surface treated in step 1, the mass fraction of the titanate coupling agent solution can be selected between 2% and 3%, the soaking time is 1 to 2 hours, and the drying temperature is adjusted between 70 and 80°C.

9. The preparation method according to claim 2, It is characterized in that In step 2, the synthesis temperature of the organic compound C varies between 50-60° C., the stirring speed is adjusted between 200-300 rpm, and the reaction time varies between 6-10 hours.

10. The preparation method according to claim 2, It is characterized in that In the synthesis process of the organic compound D in step 2, the amount of the solvent is adjusted between 40% and 50% of the total mass of the raw monomers, the polymerization temperature varies between 60 and 70° C., and the reaction time varies between 8 and 12 hours.